Astegolimab, an anti-ST2, in chronic obstructive pulmonary disease (COPD-ST2OP): a phase 2a, placebo-controlled trial. Issue 5 (May 2022) - Yousuf, Ahmed J; Mohammed, Seid; Carr, Liesl; Yavari Ramsheh, Mohammadali; Micieli, Claudia; Mistry, Vijay; Haldar, Kairobi; Wright, Adam; Novotny, Petr; Parker, Sarah; Glover, Sarah; Finch, Joanne; et al.
Summary: Background: Chronic obstructive pulmonary disease (COPD) is a heterogeneous inflammatory airway disease. The epithelial-derived IL-33 and its receptor ST2 have been implicated in airway inflammation and infection. We aimed to determine whether astegolimab, a selective ST2 IgG2 monoclonal antibody, reduces exacerbations in COPD. Methods: COPD-ST2OP was a single-centre, randomised, double-blinded, placebo-controlled phase 2a trial in moderate-to-very severe COPD. Participants were randomly assigned (1:1) with a web-based system to received 490 mg subcutaneous astegolimab or subcutaneous placebo, every 4 weeks for 44 weeks. The primary endpoint was exacerbation rate assessed for 48 weeks assessed with a negative binomial count model in the intention-to-treat population, with prespecified subgroup analysis by baseline blood eosinophil count. The model was the number of exacerbations over the 48-week treatment period, with treatment group as a covariate. Safety was assessed in the whole study population until week 60. Secondary endpoints included Saint George's Respiratory Questionnaire for COPD (SGRQ-C), FEV1, and blood and sputum cell counts. The trial was registered with ClinicalTrials.gov, NCT03615040 . Findings: The exacerbation rate at 48 weeks in the intention-to-treat analysis was not significantly different between the astegolimab group (2·18 [95% CI 1·59 to 2·78]) and the placebo group (2·81 [2·05 to 3·58]; rate ratio 0·78 [95% CI 0·53 to 1·14]; p=0·19]). In the prespecified analysis stratifying patients by blood eosinophil count, patients with 170 or fewer cells per μL had 0·69 exacerbations (0·39 to 1·21), whereas those with more than 170 cells per μL had 0·83 exacerbations (0·49 to 1·40). For the secondary outcomes, the mean difference between the SGRQ-C in the astegolimab group versus placebo group was –3·3 (95% CI –6·4 to –0·2; p=0·039), and mean difference in FEV1 between the two groups was 40 mL (–10 to 90; p=0·094). The difference in geometric mean ratios between the two groups for blood eosinophil counts was 0·59 (95% CI 0·51 to 0·69; p<0·001) and 0·25 (0·19 to 0·33; p<0·001) for sputum eosinophil counts. Incidence of treatment-emergent adverse events was similar between groups. Interpretation: In patients with moderate-to-very severe COPD, astegolimab did not significantly reduce exacerbation rate, but did improve health status compared with placebo. Funding: Funded by Genentech and National Institute for Health Research Biomedical Research Centres.